Sensitive Orbital Angular Momentum (OAM) Monitoring by Using Gradually Changing-Period Phase Grating in OAM-Multiplexing Optical Communication Systems - Yangjin Li; Jing Deng; Jianping Li; Zhaohui Li (IEEE Photonics Journal, 2016)
We propose specially designed gradually changing-period phase grating (GCPPG) and used it to monitor the orbital angular momentum (OAM) light beam. Based on GCPPG, zero-order diffraction can be eliminated, and the diffraction power can be concentrated to the first-order diffraction. In this way, the detection sensitivity of the OAM beam can be significantly improved.